Binder as well as preparation method and application thereof
By using a binder containing a polymer containing a phosphate group and a carboxy group and a one-dimensional carbon material, the problem of body phase and interface failure of layered oxide positive electrode active materials at high voltage is solved, and the stability and performance of the battery structure are improved.
Patent Information
- Application Number
- CN202510206098.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
Laminated oxide positive electrode active materials are prone to body phase and interface damage at high voltages, resulting in increased battery resistance and capacity attenuation.
A binder including a polymer and a one-dimensional carbon material is used. The polymer contains at least two branched chains connected to the carbon material. The carbon material contains phosphate groups and carboxy groups, which can form hydrogen bonds and bonds with the positive electrode active material, stabilize the interface structure and inhibit the dissolution of the transition metal.
This adhesive can significantly alleviate the body phase and interface damage problems of the positive electrode active material, and improve the structural stability and performance of the battery, including high magnification and cycling performance.
Smart Images

Figure CN119684935A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery binders, and in particular to binders and preparation methods and applications thereof. Background Art
[0002] Positive electrode active materials are important components of sodium-ion batteries and lithium-ion batteries. Among them, layered oxides such as lithium transition metal oxides and sodium transition metal oxides are the most widely used positive electrode active materials. In order to meet people's demand for high-energy density batteries, layered positive electrode materials need to have a higher cut-off voltage. However, higher voltages also make positive electrode active materials face challenges in bulk and interface, including the destruction of bulk phase caused by irreversible phase change or internal stress accumulation, corrosion of the interface between positive electrode active materials and electrolytes, and surface damage caused by transition metal dissolution. These problems will cause problems such as increased battery resistance and capacity attenuation, greatly limiting their practical applications.
[0003] In order to overcome the above problems, methods of designing high-performance layered cathode active materials, element doping and surface coating have been widely reported. Taking sodium transition metal oxides as an example, replacing the elements of the transition metal layer or sodium layer in the material with other elements can regulate the interlayer spacing and local electron density between the transition metal layer and the sodium layer, thereby inhibiting the irreversible phase change that occurs when sodium ions are embedded and extracted. Alternatively, surface modification using materials such as oxides, fluorides, and phosphates can construct a more stable cathode / electrolyte interface (CEI), protect the cathode surface from electrolyte corrosion, and reduce the dissolution of transition metal ions. However, most of these methods are complex processes and will increase battery costs, while also reducing the capacity of the battery to a certain extent.
[0004] There are also studies that optimize the binder composition, prepare a mixture of multiple active ingredients as a binder, use the chelation effect of the active ingredients in the binder to inhibit the dissolution of transition metal ions, and promote the formation of CEI film on the surface of the positive electrode material to improve the stability of the positive electrode material interface. However, this binder is a mixture, and when it is in the positive electrode slurry and when the slurry is coated on the current collector, it is difficult for the components in it to evenly act on the positive electrode active material, conductive agent, and current collector, and the degree of improvement in battery performance still needs to be improved. Summary of the invention
[0005] The purpose of the present application is to provide a binder and a preparation method and application thereof, aiming to solve the problem that the bulk phase and interface of layered oxide positive electrode active materials in the prior art are easily destroyed.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows: In a first aspect, the present application provides a binder, comprising a polymer and a one-dimensional carbon material, wherein the polymer contains at least two side chains, and the side chains are connected to the carbon material; Wherein, the carbon material further contains at least one of a phosphate group and a carboxyl group; and / or The polymer also contains at least one of a phosphate group and a carboxyl group.
[0007] The phosphate group and carboxyl group in the binder of the present application can form hydrogen bonds with the positive electrode active material, which can provide a strong bonding effect. The phosphate group and carboxyl group also form a bonding or chelating effect with the transition metal of the positive electrode active material, stabilize the interface structure of the positive electrode active material, and inhibit the dissolution of the transition metal. It also has a desolvation effect and optimizes the solid electrolyte membrane (CEI). At least two branches are connected to a one-dimensional carbon material to enhance the uniformity of polymer distribution and the stretchability of the chain segment. Then, a framework is formed between the polymer, two adjacent branches, and the carbon material. The more branches there are, the more frameworks there are, which is more conducive to enhancing the mechanical properties of the polymer chain segment. On the one hand, the binder can make the effect of the binder on the various components of the electrode more sufficient and uniform; on the other hand, the binder is combined with the surface of the positive electrode active material, and these frameworks can relieve the stress generated by the phase change of the positive electrode active material and stabilize the crystal phase of the material; it can also form a polymer nanolayer coating on the surface of the positive electrode active material to reduce the erosion of the electrolyte on the positive electrode active material. In summary, the present application can greatly alleviate the problem that the bulk phase and interface of the positive electrode active material are easily destroyed, which is conducive to the stability of the bulk phase and interface.
[0008] In a second aspect, the present application provides a method for preparing the adhesive of the above application, comprising the following steps: Performing a first cross-linking reaction on a one-dimensional carbon material raw material and a cross-linking agent to obtain a cross-linked carbon material; The cross-linked carbon material and the active polymer are subjected to a second cross-linking reaction, so that the groups of the cross-linked carbon material are bonded to the groups of the active polymer to obtain a binder; The carbon material raw material contains phosphoric acid groups and / or carboxyl groups; and the active polymer contains phosphoric acid groups and / or carboxyl groups.
[0009] The preparation method of the present application firstly conducts a first crosslinking reaction between the carbon material raw material and the crosslinking agent, so that the crosslinking agent is partially crosslinked with the phosphate group and / or carboxyl group of the carbon material raw material to obtain a crosslinked carbon material, and then conducts a second crosslinking reaction with an active polymer containing a phosphate group and / or carboxyl group, and after bonding, a branch chain connecting the polymer main chain and the carbon material can be formed, thereby obtaining the binder of the above application, which is beneficial to the stability of the bulk phase and interface of the positive electrode active material. The preparation method process is controllable, and the structure and properties of the obtained binder are stable.
[0010] In a third aspect, the present application provides a positive electrode, including a current collector and a positive electrode active layer bonded to the current collector, wherein the positive electrode active layer contains the binder of the above-mentioned application or contains the binder prepared by the preparation method of the above-mentioned application.
[0011] The binder of the present application can strongly bond with the positive electrode active material, the conductive agent, and the current collector, and the action is fully and uniformly, which is more conducive to the bulk and interface stability of the positive electrode active material, and also has extremely high ionic conductivity and electronic conductivity. Therefore, the positive electrode of the present application contains the binder, the positive electrode has a stable structure, and has high rate and cycle performance.
[0012] In a fourth aspect, the present application provides a secondary battery, the secondary battery comprising the positive electrode of the above-mentioned application.
[0013] The secondary battery of the present application includes the positive electrode of the above-mentioned application, so the positive electrode structure of the secondary battery is stable and also has good rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0015] Figure 1 is a schematic diagram of a cross-linking reaction occurring during the preparation of the binder in Example A1 of the present application; Figure 2 This is an infrared spectrum of some raw materials and the prepared adhesive in Example A1 of the present application; Figure 3 It is a comparison chart of the cycle performance of Example B1, Comparative Example B1, and Comparative Example B2 of the present application; Figure 4 It is a rate performance comparison chart of Example B1, Comparative Example B1, and Comparative Example B2 of the present application. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0017] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0018] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0019] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0020] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0021] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0022] In a first aspect, an embodiment of the present application provides a binder, comprising a polymer and a one-dimensional carbon material, wherein the polymer contains at least two side chains, and the side chains are connected to the carbon material; Wherein, the carbon material further contains at least one of a phosphate group and a carboxyl group; and / or The polymer also contains at least one of a phosphate group and a carboxyl group.
[0023] The phosphate group and carboxyl group in the binder of the embodiment of the present application can form hydrogen bonds with the positive electrode active material, which can provide a strong bonding effect. The phosphate group and carboxyl group also form a bonding or chelating effect with the transition metal of the positive electrode active material, stabilize the interface structure of the positive electrode active material, and inhibit the dissolution of the transition metal; they also have a desolvation effect and optimize the solid electrolyte membrane (CEI). The polymer in the binder is connected to the carbon material through the branch chain to form a whole rather than a mixture. The carbon material is one-dimensional, and at least two branches of the polymer are connected to the one-dimensional carbon material to enhance the uniformity of the polymer distribution and the stretchability of the chain segment. Then, a framework is formed between the polymer, the two adjacent branches, and the carbon material. The more branches there are, the more frameworks there are, and the more conducive it is to enhance the mechanical properties of the polymer chain segment. On the one hand, the binder makes the effect of the binder on the various components of the electrode (positive electrode active material, conductive agent and other components) more sufficient and uniform; on the other hand, the binder is combined with the surface of the positive electrode active material, and these frameworks can relieve the stress generated by the phase change of the positive electrode active material and stabilize the crystal phase of the material; polymer nanolayers can also be formed on the surface of the positive electrode active material to reduce the erosion of the electrolyte on the positive electrode active material. In summary, the embodiments of the present application can greatly alleviate the problem that the bulk phase and interface of the positive electrode active material are easily destroyed, which is beneficial to the stability of the bulk phase and interface.
[0024] In addition to the above effects on the positive electrode active material, in the positive electrode, the phosphate group and carboxyl group also form hydrogen bonds with the conductive agent and the current collector, providing a strong bonding effect and improving the stability of the positive electrode sheet; the stretching of the polymer chain segment of the binder is also conducive to a more complete and uniform interaction between the binder and the conductive agent and the current collector. The phosphate group also improves the ionic conductivity of the binder such as lithium ions and sodium ions, while the carbon material improves the electronic conductivity of the binder. Therefore, the binder also has extremely high ionic conductivity and electronic conductivity, which is conducive to improving the performance of the positive electrode and the battery such as rate and cycle.
[0025] About polymers: In some embodiments, the main chain of the polymer contains at least one of an alkyl group, an alkenyl group, an alkynyl group, an ether group, an ester group, a ketone group, an amide group, a phenyl group, and a sugar group, and the main chain can be optionally formed by an alkyl group.
[0026] In some embodiments, the side chain includes at least one of amide group bonding, ester group bonding, carboxyl-carboxyl hydrogen bonding, phosphate ester bonding, phosphate-carboxyl hydrogen bonding, anhydride bonding, and ether bonding. Of course, the side chain may also include organic groups such as alkyl groups. The bonding or hydrogen bonding of these groups in the side chain further improves the stability of the side chain, which is beneficial to the stretching of the polymer chain segment and the improvement of the strength and distribution uniformity of the framework, thereby further facilitating the bulk and interface stability of the positive electrode active material. Ideally, the main chain of the polymer stretches in a direction parallel to the carbon material, the side chain connects the polymer main chain and the carbon material, and the next side chain connects at the next position of the polymer main chain and the carbon material to form an orderly periodically repeated framework, which forms a quadrilateral-like structure (since the side chain and the main chain are not absolute straight lines, for a visual understanding, two adjacent side chains are regarded as two sides, and the polymer main chain and the carbon material in between are regarded as the other two sides, as a quadrilateral-like structure, rather than a strict quadrilateral structure in a geometric sense). The optional side chains are shorter, with the number of carbon atoms in a side chain ≤ 100. Such shorter side chains are conducive to the main chain of the polymer stretching in the parallel direction of the carbon material, which is conducive to the formation of frames one by one, and also improves the strength of the frame, thereby improving the binder's effect of stabilizing the bulk and interface of the positive electrode active material. If the side chains are shorter or longer, the side chains may be entangled, and even the interaction between the polymer main chain and the carbon material is weak, which is not conducive to the stretching of the polymer chain segments and the stability of the frame structure.
[0027] About Carbon Materials: The carbon material is one-dimensional, i.e. linear, and in some embodiments, the carbon material includes at least one of carbon nanotubes, carbon fibers, and graphene nanoribbons. Among them, the carbon nanotubes can be single-walled carbon nanotubes or multi-walled carbon nanotubes. It should be noted that, since the carbon material is connected to the side chains of the polymer, these carbon materials do not exist in isolation in the binder, and cannot be understood as having isolated carbon nanotubes, carbon fibers, and other materials, but form a whole with the polymer. These types of carbon materials are conducive to the stretching of polymer segments and improving the strength of the framework, which is conducive to the stability of the bulk phase and interface of the positive active material. At the same time, these one-dimensional carbon materials are also conducive to improving the mechanical properties of the binder. The carbon material itself also has a strong electrical conductivity, enriching the conductive network of the bond, which is conducive to improving the conductivity of the binder.
[0028] The aspect ratio of the carbon material may be (10-1000000): 1, and in the exemplary embodiment, may include but not be limited to any ratio of 1000: 1, 5000: 1, 50000: 1, 100000: 1 or any range between two ratios. The length may be 10-1000000 nm, and the diameter may be 0.8-100 nm.
[0029] About the entire binder: In some embodiments, the molar ratio of polymer to carbon material is (1-100):1. In the exemplary embodiment, it may include but is not limited to any ratio of 100:1, 10:1, 2:1, 1:1 or any range between two ratios. The polymers and carbon materials at these molar ratios are more suitable for the ratio of binding components and conductive components in the positive electrode material system of the battery. Under these molar ratios, from a microscopic point of view, mainly one carbon material can connect multiple polymer molecules, and one polymer molecule can connect multiple carbon materials. The one-dimensional carbon material continuously guides the stretching of the polymer chain segments, thereby improving the effect of the binder in stabilizing the bulk and interface of the positive electrode active material.
[0030] In some embodiments, the phosphate group in the binder can be on the main chain of the polymer, on the side chain of the polymer, on other side chains of the polymer (the side chain is not connected to the carbon material), or on the surface of the carbon material; the carboxyl group can be on the main chain of the polymer, on the side chain of the polymer, on the side chain of the polymer (the side chain is not connected to the carbon material), or on the surface of the carbon material. In the embodiment, the molar proportion of the phosphate group in the binder is 20% to 50%, which may include but is not limited to any value of 10%, 20%, 30%, 40%, 50% or a range between any two values, and the molar proportion of the carboxyl group in the binder is 30% to 70%, which may include but is not limited to any value of 30%, 40%, 50%, 60%, 70% or a range between any two values. These molar proportions of phosphate groups and carboxyl groups are further conducive to the formation of hydrogen bonds between the binder and the positive electrode active material, the conductive agent, and the current collector, providing a strong bonding effect; they are conducive to forming a bonding or chelating effect with the transition metal of the positive electrode active material, stabilizing the interface structure of the positive electrode active material, and inhibiting the dissolution of the transition metal; and they are more conducive to improving the ionic conductivity of the binder such as lithium ions and sodium ions.
[0031] Finally, the binder of the embodiment of the present application can use water and other common solvents that are inexpensive and environmentally friendly as dispersants, getting rid of the problem of the traditional binder solvent N-methylpyrrolidone (NMP) being toxic and expensive.
[0032] The second aspect of the present application embodiment provides a method for preparing the adhesive of the above application embodiment, comprising the following steps: S10: performing a first cross-linking reaction on the one-dimensional carbon material raw material and a cross-linking agent to obtain a cross-linked carbon material; S20: performing a second cross-linking reaction on the cross-linked carbon material and the active polymer, so that the groups of the cross-linked material are bonded to the groups of the active polymer to obtain a binder.
[0033] The carbon material raw material in step S10 contains phosphoric acid groups and / or carboxyl groups; and the active polymer in step S20 contains phosphoric acid groups and / or carboxyl groups.
[0034] The preparation method of the embodiment of the present application firstly conducts a first crosslinking reaction between the carbon material raw material and the crosslinking agent, so that the crosslinking agent is partially crosslinked with the phosphate group and / or carboxyl group of the carbon material raw material to obtain a crosslinked material, and then conducts a second crosslinking reaction with an active polymer containing a phosphate group and / or carboxyl group, and after bonding, a branch chain connecting the polymer main chain and the carbon material can be formed, thereby obtaining the binder of the embodiment of the present application, which is beneficial to the stability of the bulk phase and interface of the positive electrode active material. The preparation method process is controllable, and the structure and properties of the obtained binder are stable.
[0035] Step S10: This step is a step for performing the first cross-linking reaction. The type and aspect ratio of the carbon material raw material can refer to the type and parameters of the carbon material above. The carbon material raw material contains phosphate groups and / or carboxyl groups. Therefore, the carbon material raw material can be phosphorylated carbon nanotubes, phosphorylated carbon fibers, carboxylated carbon nanotubes, carboxylated carbon fibers and other raw materials. The carbon material raw material can also contain both phosphate groups and carboxyl groups. In the carbon material raw material, the mass percentage of phosphate groups and carboxyl groups is 20% to 80%.
[0036] The cross-linking agent contains at least two functional groups. In some embodiments, the functional groups include at least one of diimine, isocyano, carboxyl, hydroxyl, and amino. When the carbon material raw material contains carboxyl, the imine can form an amide group with the carboxyl, the isocyano can form an amide group with the carboxyl, the carboxyl can form an anhydride group with the carboxyl, the hydroxyl can form an ester group with the carboxyl, and the amino can form an amide group with the carboxylic acid. When the carbon material raw material contains a phosphoric acid group, the diimine can form an amide with phosphoric acid, the hydroxyl can form a phosphate ester group with phosphoric acid, and the phosphoric acid and the carboxylic acid can produce a hydrogen bond.
[0037] The crosslinking agent may be an aqueous crosslinking agent. In some embodiments, when the crosslinking agent contains diimide, it may be polycarbodiimide. When the crosslinking agent contains isocyanate, it may be isocyanate. In the exemplary embodiment, it may include at least one of toluene diisocyanate and hexamethylene diisocyanate. When the crosslinking agent contains carboxyl, it may be at least one of citric acid, maleic acid, and malonic acid. When the crosslinking agent contains hydroxyl, it may be at least one of glycerol, ethylene glycol, and xylitol. When the crosslinking agent contains amino, it may be at least one of phenylenediamine and ethylenediamine. In addition, the crosslinking agent may also contain two or more different functional groups.
[0038] The first cross-linking reaction can mix the raw materials in a solvent and continue to stir, and the solvent can be at least one of deionized water, ethanol, dichloromethane, and tetrahydrofuran. In some embodiments, the temperature of the first cross-linking reaction can be 20 to 160°C, and the reaction time can be 0.5 to 12 hours. After the first cross-linking reaction, it is ideal that some functional groups in the cross-linking agent have been bonded to the carbon material raw material, and other functional groups in the cross-linking agent form a large number of cross-linking points on the surface of the cross-linked carbon material, which can participate in the subsequent second cross-linking reaction.
[0039] Step S20: This step is a step of further crosslinking the active polymer with the crosslinked carbon material. The crosslinked carbon material contains functional groups in the crosslinking agent. Since the active polymer contains phosphoric acid groups and / or carboxyl groups, these functional groups can be bonded to the active polymer. The specific bonding method can refer to the statement of the phosphoric acid groups and / or carboxyl groups and the crosslinking agent forming amide group bonding, ester bonding, anhydride bonding, phosphate ester bonding, etc. in step S10 above. Therefore, in the binder obtained by the first crosslinking reaction and the second crosslinking reaction, a morphology in which the polymer main chain and the carbon material are connected through the polymer side chains is formed, which is conducive to the stretching of the polymer chain segments and the formation of the framework, and is conducive to the stability of the bulk phase and interface of the positive electrode active material.
[0040] The second cross-linking reaction can mix the raw materials and continue to stir. In some embodiments, the temperature of the second cross-linking reaction can be 20 to 160°C, and the reaction time can be 0.5 to 12 hours. The temperature and reaction time can be the same or different from the temperature and reaction time of the first cross-linking reaction. In some embodiments, the mass ratio of the carbon material raw material, the cross-linking agent, and the active polymer can be (1 to 20): (1 to 50): (30 to 70). In the exemplary embodiment, it can include but is not limited to (1 or 5 or 10 or 20): (1 or 5 or 10 or 20 or 50): (30 or 40 or 50 or 60 or 70) any ratio or the range between any two ratios. Different amounts of cross-linking agent can adjust the cross-linking density of the obtained binder, thereby regulating the physical and chemical properties of the binder.
[0041] In some embodiments, the active polymer includes a carboxyl-containing polymer, and a polyphosphoric acid material is also added to the second cross-linking reaction, so that the carboxyl-containing polymer, the cross-linking agent, and the polyphosphoric acid material undergo a third cross-linking reaction. In this way, the carboxyl-containing polymer and the cross-linked carbon material undergo a second cross-linking reaction, and the polyphosphoric acid material also undergoes a third cross-linking reaction with the carboxyl-containing polymer through the cross-linking agent. In addition, the polyphosphoric acid material can also directly form a phosphate group-carboxyl hydrogen bond with the carboxyl-containing polymer, which is beneficial to introduce abundant carboxyl and phosphate groups into the prepared binder, further beneficial to the hydrogen bonding of the binder with the positive active material, the conductive agent, and the current collector, and improves the bonding performance; it is also further beneficial to stabilize the interface structure of the positive active material and inhibit the dissolution of the transition metal; it is further beneficial to improve the ionic conductivity of the bonding.
[0042] In some embodiments, the carboxyl-containing polymer includes at least one of polyacrylic acid, polyacrylic acid salt, hyaluronic acid, hyaluronate, alginic acid, and alginate (lithium, sodium, potassium, magnesium, calcium, zinc or aluminum salt). The mass proportion of carboxyl groups in the carboxyl-containing polymer can be 20% to 65%. These carboxyl-containing polymers with high carboxyl content are beneficial to improving the bonding performance of the binder and improving the stability of the bulk and interface of the positive electrode active material. In the exemplary embodiment, the weight average molecular weight of the carboxyl-containing polymer can be greater than 300,000.
[0043] In some embodiments, the polyphosphoric acid material includes at least one of polyphosphoric acid, phytic acid, polymetaphosphoric acid, alkyl polyphosphoric acid, phytate (lithium, sodium, potassium, magnesium, calcium, zinc or aluminum salt), aminotrimethylphosphoric acid, diethylenetriamine pentamethylphosphonic acid, polyphosphate, polymetaphosphate, and alkyl polyphosphate. These polyphosphoric acid materials contain abundant phosphate groups. After the third cross-linking reaction with the carboxyl-containing polymer and the cross-linking agent, these phosphate groups increase the phosphate group content in the obtained binder, which is beneficial to improve the binding performance of the binder, improve the stability of the bulk phase and interface of the positive electrode active material, and improve the ion conductivity of the binder.
[0044] In some embodiments, the mass ratio of the carboxyl-containing polymer to the polyphosphoric acid material is (30-70): (20-50). In exemplary embodiments, the mass ratio may include but is not limited to any ratio of (30 or 40 or 50 or 60 or 70): (20 or 30 or 40 or 50) or a range between any two ratios.
[0045] In some embodiments, after the second cross-linking reaction, a step of pH adjustment is further included. The pH adjustment is mainly to meet the pH requirements of the positive electrode slurry and the current collector. The pH adjustment method can be to add a pH adjustment agent to the product of the second cross-linking reaction for adjustment. The pH adjustment agent can be at least one of LiOH, NaOH, and KOH, so that the final pH of the obtained binder is 4 to 8 at room temperature. The concentration of the final binder is 1 to 50 wt%.
[0046] A third aspect of the embodiments of the present application provides a positive electrode, including a current collector and a positive electrode active layer bonded to the current collector, wherein the positive electrode active layer contains the binder of the above embodiments of the present application or contains the binder prepared by the preparation method of the above embodiments of the present application.
[0047] The binder of the embodiment of the present application can be strongly bonded to the positive electrode active material, the conductive agent, and the current collector, and the action is fully and uniformly, which is more conducive to the bulk and interface stability of the positive electrode active material, and also has extremely high ionic conductivity and electronic conductivity. Therefore, the positive electrode of the embodiment of the present application contains the binder, the structure of the positive electrode is stable, and has high rate and cycle performance.
[0048] In some embodiments, the positive electrode active layer contains a positive electrode active material, which is a lithium ion layered positive electrode material, which can be selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, fluorolithium vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. The positive electrode active material can also be a sodium ion layered positive electrode material that satisfies the chemical formula Na x At least one of TMO2 (TM=one or more of Co, Mn, Ni, Li, Ti, Fe, Cr, Cu, V).
[0049] Compared with the prior art, since the binder in the above application embodiment has extremely high electronic conductivity, a conductive agent may not be added to the positive electrode active layer, or a conductive agent may be appropriately added, which may include at least one of conductive graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.
[0050] In the embodiment, the positive electrode sheet preparation process can be: the positive electrode active material, the conductive agent (optional) and the binder are mixed, and water or other solvents (ethanol, NMP) are added according to the solid content of the system to adjust the solid content of the system to obtain a positive electrode slurry, the proportion of the binder (excluding the mass of the binder's own solvent) in the slurry is 1-20wt%, the proportion of the conductive agent is 0-20wt%, and the solid content of the slurry is 0.3-1 g / mL. The positive electrode slurry is coated on the current collector, and further, the current collector is aluminum foil or other widely used lithium ion or sodium ion battery positive electrode current collector. Finally, the positive electrode sheet is prepared by drying, rolling, die cutting and other steps.
[0051] A fourth aspect of an embodiment of the present application provides a secondary battery, the secondary battery comprising the positive electrode of the above embodiment of the present application.
[0052] The secondary battery of the present application embodiment includes the positive electrode of the above application embodiment, so the positive electrode structure of the secondary battery is stable and has good rate performance and cycle performance. The secondary battery also includes necessary components such as the negative electrode, separator and electrolyte, and of course other necessary or auxiliary components.
[0053] The following describes the invention in conjunction with specific embodiments.
[0054] Example A1 This embodiment provides a binder and a preparation method thereof, please refer to Figure 1 As shown, the preparation method includes the following steps S1-S2: S1: First cross-linking reaction First, 0.5 g of carboxylated multi-walled carbon nanotubes (carbon material raw material) containing 50% carboxyl groups by mass was dissolved in 100 mL of deionized water, and then 2.5 g of polycarbodiimide (cross-linking agent, excess) was added to carry out the first step of cross-linking reaction. The cross-linking temperature was 80 ° C, and stirring was continued for 6 h to obtain cross-linked carbon nanotubes.
[0055] S2: Second cross-linking reaction 5 g of polyacrylic acid (carboxyl-containing polymer) and 2 g of sodium polyphosphate (polyphosphoric acid material) were added to the cross-linked carbon nanotubes obtained in step S1 to carry out the second cross-linking reaction. During the process, not only the cross-linked carbon nanotubes and polyacrylic acid were cross-linked, but also the polyacrylic acid and the cross-linking agent and sodium polyphosphate were cross-linked. The cross-linking temperature was 80°C. Stirring was continued for 6 h to obtain a uniform, transparent, viscous liquid. 1 M sodium hydroxide was added to the uniformly dispersed system to adjust the pH value to 7 at room temperature to obtain a binder.
[0056] Example A2 This embodiment provides a binder and a preparation method thereof, which is different from Embodiment A1 only in that the polycarbodiimide in step S1 is replaced with propylene glycol, and the rest is the same.
[0057] Example A3 This embodiment provides a binder and a preparation method thereof, which is different from Embodiment A1 only in that the polyacrylic acid in step S2 is replaced with hyaluronic acid, and the rest is the same.
[0058] Example A4 This embodiment provides a binder and a preparation method thereof, which is different from Embodiment A1 only in that the sodium polyphosphate in step S2 is replaced by aminotri(methylene)phosphoric acid, and the rest is the same.
[0059] Example A5 This embodiment provides a binder and a preparation method thereof, which is different from the embodiment A1 only in that the carboxylated multi-walled carbon nanotubes in step S1 are replaced with phosphorylated carbon nanotubes, and the rest are the same.
[0060] Example A6 This embodiment provides a binder and a preparation method thereof, which is different from Embodiment A6 only in that the polycarbodiimide in step S1 is replaced with propylene glycol, and the rest is the same.
[0061] Comparative Example A1 The binder provided in this comparative example is polyvinylidene fluoride (PVDF) commonly used in positive electrodes.
[0062] Comparative Example A2 This comparative example provides a binder in the form of a mixture. The raw materials are the other raw materials in Example A1 except the cross-linking agent. 0.5 g of carboxylated single-walled carbon nanotubes, 5 g of polyacrylic acid, and 2 g of sodium polyphosphate are directly dissolved in 100 mL of deionized water and stirred for 10 h to obtain a mixed binder.
[0063] The differences between Examples A1 to A6 and Comparative Examples A1 to A2 are shown in Table 1.
[0064] Table 1
[0065] Sodium ion battery example: The binders provided in the above-mentioned Examples A1 to A6 and Comparative Examples A1 to A2 are respectively assembled into positive electrodes and sodium ion batteries according to the following methods: Positive electrode: The positive electrode active material is a sodium-based P2-type layered positive electrode material Na 0.7 Li 0.1 Cu 0.1 Mg 0.1 Mn 0.7 O2. The positive electrode active material, binder, and super P conductive carbon were put into a mixing tank at a mass ratio of 80:10:10, zirconium beads were added to improve the mixing efficiency, deionized water was added to the mixing tube at a solid content of 0.4 g / mL, and a micro mixer was used to stir it into an electrode slurry with uniform composition.
[0066] The prepared electrode slurry was scraped onto the surface of the aluminum foil using a coating machine to form a 0.2 mm thick slurry film. The electrode sheet was immediately transferred to a 60°C forced air drying oven for drying for 6 hours, and then the baked electrode sheet was transferred to a vacuum oven and vacuum-baked at 110°C for 12 hours to remove residual moisture. The electrode sheet was then rolled with a roller press and cut into a circular electrode sheet with a diameter of 12 mm using a cutting machine.
[0067] Assembly: Assemble 2032 button cells in an argon glove box in the order of positive electrode shell, positive electrode sheet, 50 μL electrolyte, glass fiber, 50 μL electrolyte, sodium sheet, gasket, spring sheet, and negative electrode shell.
[0068] Among them, the binder of Example A1 is used to prepare the sodium ion battery of Example B1, the positive electrode material of Example A2 is used to prepare the sodium ion battery of Example B2, and so on, until the binder of Comparative Example A2 is used to prepare the sodium ion battery of Comparative Example B2.
[0069] Related performance tests and result analysis 1. Reaction process like Figure 1 As shown, the cross-linking agent in Example A1 first undergoes a first cross-linking reaction with the carboxylated carbon nanotubes, and the carboxyl groups on the surface of the carboxylated carbon nanotubes react with the carbodiimide groups of the cross-linking agent to generate amide groups, thereby generating a large number of cross-linking points on the carbon nanotubes. Subsequently, polyphosphoric acid material and carboxyl-containing polymer are added to undergo a second cross-linking reaction, and the carboxyl-containing polymer with a high degree of polymerization reacts with the carbon nanotubes containing a large number of cross-linking points to form an ordered series of quadrilateral-like (closer to a trapezoid in observation) frameworks, and the polyphosphoric acid material also reacts with the cross-linking agent to generate amide groups and then cross-links on the carboxyl-containing polymer, or the polyphosphoric acid material directly bonds to the carboxyl-containing polymer through hydrogen bonds, thereby being incorporated into the entire binder.
[0070] The final cross-linking agent includes carbon nanotubes and polymers, and several branches of the polymer connect the carbon nanotubes. The binder also contains abundant phosphate groups and carboxyl groups. The polymer segments in the binder are more stretched under the guidance of the carbon nanotubes, and these frameworks work together to make the binder act evenly and fully on the positive electrode active material. These frameworks can also relieve the stress caused by the phase change of the positive electrode active material and stabilize the crystal phase of the material; they also have a desolvation effect and optimize the solid electrolyte membrane (CEI); they can also form a polymer nanolayer coating on the surface of the positive electrode active material to reduce the erosion of the electrolyte on the positive electrode active material.
[0071] 2. Structural analysis Figure 2 The infrared spectra of polyacrylic acid, carboxylated carbon nanotubes, polycarbodiimide, polyphosphoric acid and the prepared binder in Example A1 show that polyacrylic acid and carboxylated carbon nanotubes have an infrared spectrum of 1700 cm -1 There is an obvious infrared absorption peak of C=O near the polycarbodiimide at 1600 cm -1 The vibration peak of the C=N functional group is shown, and the final composite binder has a peak at 1500 cm -1 A new infrared absorption peak of the CN functional group appears nearby, indicating that the carboxylic acid functional group reacts successfully with the cross-linking agent to form an amide bond.
[0072] 3. Cycle performance At 25°C, 1.5-4.5 V charge and discharge voltage conditions, 1C charge and discharge rate, and a nominal specific capacity of 100 mAh / g, a cycle stability test was performed, wherein the results of Example B1, Comparative Example B1, and Comparative Example B2 are as follows: Figure 3 As shown, Figure 3 The "conductive ion-conducting ladder binder" is the sodium ion battery of Example B1 made with the binder of Example A1, "PVDF" corresponds to the corresponding proportions A1 and B1, and the "mixed binder" corresponds to the corresponding proportions A2 and B2. Figure 2 It can be seen that the performance of comparative example B2 is better than that of comparative example B1. However, compared with the two comparative examples, the cycle stability of the sodium ion battery of embodiment B1 is significantly higher.
[0073] 4. Rate performance Under the conditions of 25°C and 1.5-4.5 V charge and discharge voltage, the rate performance at 1C charge and discharge rate was tested, the nominal specific capacity was 100 mAh / g, and the charge and discharge currents were set at 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 10C, 20C and 30C respectively, and the half-cell was cycled at 0.5C after the rate cycle to recover. Among them, the results of Example B1, Comparative Example B1 and Comparative Example B2 are as follows Figure 4 As shown, Figure 4 The "conductive ion-conducting ladder binder" is the sodium ion battery of Example B1 made with the binder of Example A1, "PVDF" corresponds to the corresponding proportions A1 and B1, and the "mixed binder" corresponds to the corresponding proportions A2 and B2. Figure 4 It can be seen that the performance of comparative example B2 is better than that of comparative example B1. However, compared with the two comparative examples, the rate performance of the sodium ion battery of embodiment B1 is significantly higher.
[0074] Therefore, compared with the existing commonly used PVDF binder and the optimized and adjusted physical mixed binder, the binder of the present application can fully interact with the positive electrode active material when used for the positive electrode, relieve the stress generated by the phase change of the positive electrode active material, stabilize the material crystal phase, inhibit the dissolution of transition metals, optimize the solid electrolyte membrane (CEI), and reduce the erosion of the electrolyte, which is beneficial to the stability of the positive electrode active material phase and interface. The binder also has high ionic conductivity and electronic conductivity, which is beneficial to improving the rate and cycle performance of the battery.
[0075] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A binder, characterized in that: The invention comprises a polymer and a one-dimensional carbon material, wherein the polymer contains at least two branch chains, and the branch chains are connected to the carbon material; Wherein, the carbon material further contains at least one of a phosphate group and a carboxyl group; and / or The polymer also contains at least one of a phosphate group and a carboxyl group.
2. The adhesive according to claim 1, characterized in that: The side chains include at least one of amide group bonding, ester group bonding, carboxyl-carboxyl group hydrogen bonding, phosphate group bonding, phosphate group-carboxyl group hydrogen bonding, anhydride group bonding, and ether group bonding; And / or, the main chain of the polymer contains at least one of an alkyl group, an alkenyl group, an alkynyl group, an ether group, an ester group, a ketone group, an amide group, a phenyl group, and a sugar group.
3. The adhesive according to claim 1 or 2, characterized in that: The molar ratio of the polymer to the carbon material is (1-100): 1; and / or, the molar proportion of the phosphoric acid groups in the binder is 20% to 50%; and / or, the molar proportion of the carboxyl groups in the binder is 30% to 70%; And / or, the carbon material includes at least one of carbon nanotubes, carbon fibers, and graphene nanoribbons; And / or, the aspect ratio of the carbon material is (10-1,000,000):
1.
4. A method for preparing the adhesive according to any one of claims 1 to 3, characterized in that: The steps include: Performing a first cross-linking reaction on a one-dimensional carbon material raw material and a cross-linking agent to obtain a cross-linked carbon material; The cross-linked carbon material and the active polymer undergo a second cross-linking reaction, so that the groups of the cross-linked carbon material are bonded to the groups of the active polymer to obtain a binder; Wherein, the carbon material raw material contains phosphoric acid groups and / or carboxyl groups; and the active polymer contains phosphoric acid groups and / or carboxyl groups.
5. The preparation method according to claim 4, characterized in that: The cross-linking agent contains at least two functional groups, and the functional groups include at least one of diimide, isocyano, carboxyl, hydroxyl, and amino; and / or, the cross-linking agent comprises at least one of polycarbodiimide, isocyanate, sodium tricyanomethanide, citric acid, maleic acid, malonic acid, glycerol, ethylene glycol, xylitol, phenylenediamine, and ethylenediamine; And / or, the mass ratio of the carbon material raw material, the cross-linking agent, and the active polymer is (1-20): (1-50): (30-70).
6. The preparation method according to claim 4 or 5, characterized in that: The active polymer includes a carboxyl-containing polymer, and a polyphosphoric acid material is further added into the second cross-linking reaction, so that the carboxyl-containing polymer, the cross-linking agent and the polyphosphoric acid material undergo a third cross-linking reaction.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the carboxyl-containing polymer to the polyphosphoric acid material is (30-70): (20-50); And / or, the polyphosphoric acid material includes at least one of polyphosphoric acid, phytic acid, polymetaphosphoric acid, alkyl polyphosphoric acid, phytate, aminotri(methylene)phosphoric acid, diethylenetriaminepenta(methylene)phosphonic acid, polyphosphate, polymetaphosphate, and alkyl polyphosphate; and / or, the carboxyl-containing polymer comprises at least one of polyacrylic acid, polyacrylic acid salt, hyaluronic acid, hyaluronate, alginic acid, and alginate; and / or, the weight average molecular weight of the carboxyl-containing polymer is greater than 300,000; And / or, the mass proportion of carboxyl groups in the carboxyl-containing polymer is 20% to 65%.
8. The preparation method according to any one of claims 4, 5 or 7, characterized in that: The temperature of the first cross-linking reaction and the second cross-linking reaction is the same or different, and the reaction time is the same or different, and is 0.5 to 12 hours; And / or, after the second cross-linking reaction, a step of adjusting pH is further included.
9. A positive electrode, characterized in that: The invention comprises a current collector and a positive electrode active layer bonded to the current collector, wherein the positive electrode active layer contains the binder according to any one of claims 1 to 3 or contains the binder prepared by the preparation method according to any one of claims 4 to 8.
10. A secondary battery, characterized in that: The secondary battery includes the positive electrode as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing cross-linking waterborne adhesive for lithium ion batteries
CN107793967A
Preparation method of in-situ cross-linked three-dimensional net-shaped binder for lithium ion battery and application method of binder
CN109921023A
Composite binder, preparation method, application, negative pole piece and battery
CN118620551A
Cured material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2024122209A